2022 IEEE International Conference on Evolving and Adaptive Intelligent Systems (EAIS) 2022
DOI: 10.1109/eais51927.2022.9787753
|View full text |Cite
|
Sign up to set email alerts
|

Online Monitoring of Stance from Tweets: The case of Green Pass in Italy

Abstract: Stance detection on social media has attracted a lot of attention in the last few years, as opinionated posts are an invaluable source of information which can possibly be exploited in dedicated systems. This is especially true in the case of particularly polarizing topics for which there is no clear consensus among population. In this paper, we focus on one of these topics, namely the EU digital COVID certificate (also known as Green Pass), with the objective of uncovering the stance towards it in a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In a study among Italian parents, Cusinato et al (2020) found that lockdown measures and changes in daily routine negatively affected parents' psychological dimensions. To conclude, the foregoing leads to the following hypotheses: H1: Perceived Covid-19-Crisis Intensity is positively related to parental burnout Furthermore, we expect that societal debates and the polarization in Italian society (Bondielli et al, 2022;Spitale et al, 2022) may trickle down and create tensions in families. We argue that diverging attitudes concerning Covid-19 vaccination and vaccination passports may create additional psychological stressors for parents.…”
Section: Perceived Covid-19-crisis Intensitymentioning
confidence: 97%
See 2 more Smart Citations
“…In a study among Italian parents, Cusinato et al (2020) found that lockdown measures and changes in daily routine negatively affected parents' psychological dimensions. To conclude, the foregoing leads to the following hypotheses: H1: Perceived Covid-19-Crisis Intensity is positively related to parental burnout Furthermore, we expect that societal debates and the polarization in Italian society (Bondielli et al, 2022;Spitale et al, 2022) may trickle down and create tensions in families. We argue that diverging attitudes concerning Covid-19 vaccination and vaccination passports may create additional psychological stressors for parents.…”
Section: Perceived Covid-19-crisis Intensitymentioning
confidence: 97%
“…Furthermore, we expect that societal debates and the polarization in Italian society ( Bondielli et al, 2022 ; Spitale et al, 2022 ) may trickle down and create tensions in families. We argue that diverging attitudes concerning Covid-19 vaccination and vaccination passports may create additional psychological stressors for parents.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation